Influence of Profitability, Audit Quality, and Corporate Governance on Earnings Management - Hansel Angga Winata; Febryanti Simon (Pandawan, 2024)
This study investigates the impact of profitability, audit quality, the composition of independent board commissioners, managerial ownership, and institutional ownership on earnings management. The population for this research comprises all manufacturing companies listed on the Indonesia Stock Exchange (BEI) between 2019 and 2021. It adopts a correlational research design with naquantitative approach. Data collection involves secondary data obtained through purposive sampling. The sample size consists of 32 companies, resulting in 96 observations. The study employs various analytical techniques, including classic assumption tests such as normality, heteroscedasticity, multicollinearity, and autocorrelation tests. Hypothesis testing is conducted using multiple regression analysis with SPSS version 26. Findings reveal that managerial ownership negatively influences earnings management, exhibiting a significant result of 0.036. Conversely, profitability, audit quality, the composition of the independent board of commissioners, and institutional ownership do not significantly affect earnings management, as their significance results exceed 0.05.